ANALISIS DAERAH POTENSI LONGSOR KALIJAGA SELATAN MENGGUNAKAN GEOLISTRIK WENNER - Syarifatul Ulfah; Agus Winardi; Nuraini Nanda i (SainsTech Innovation Journal, 2025)
Landslides are a disaster that can occur at any time without warning. Therefore, identifying areas with the potential to become slip surfaces is a crucial mitigation step. The risks and losses from these disasters can be minimized or even avoided. One method used to identify potential landslide areas is the geoelectric method. This study used the Wenner configuration resistivity method. This study, conducted on two tracks, indicated the potential for slip surfaces ranging from moderate to very deep. With resistivity values ??of 23–503 ohm.m, the soil is interpreted as clay and is indicated as a potential landslide area at a depth of 2–15 meters